Peningkatan Pengetahuan Pada Ibu Yang Memiliki Balita Tentang Metode Kangguru dan Musik Wizard di Rumah Sakit Setio Husodo Kisaran - Lestari, Ika; Joharmi; Sintania, Wiwin; Erwika (Cattleya Darmaya Fortuna, 2022)
A complication that often occurs in LBW babies is hypothermia. Preventing hypothermia is done by regulating the body temperature of neonates. One of these methods is to provide an environment with a neutral temperature (thermal zone neutral area) for newborn babies, or it can be done with the kangaroo method of care (PMK) where the mother's skin will be in direct contact with the baby's skin to achieve the baby's ideal temperature (skin to skin). contact) (Anantasari and Ririn, 2019). Kangaroo Method Care (FMD) has been proven to be beneficial for parents and babies. Assistance that is often used in care in the newborn intensive care unit includes music therapy and PMK. Many studies have been conducted on nurses who have used PMK in LBW or premature populations for long periods of time, and the results have been physiologically beneficial. If music therapy is added to PMK for LBW babies, the impact of therapy on parents will be more pronounced (Olii, N., 2019). Music therapy is a successful treatment for alleviating physical, psychological, social and spiritual life problems and for comfort (Rahmawati, 2018). Neuroendocrine and sympathetic nervous system activity will be reduced by music, which will decrease heart rate, pulse rate, and respiratory rate. Music of all genres, including classical, popular, and relaxation songs, can be used as therapy. However, songs or music with a speed of around 60 beats per minute are highly recommended (Putriana, 2018). The benefits of Mozart classical music therapy can help improve physical, psychological, social and spiritual health problems. According to research, the tones and sounds of music match brain vibrations so that they can improve brain function better (Darma, I., Y., et al. 2022).